2017
DOI: 10.1186/s41016-016-0067-y
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism-hyperpyrexia syndrome after withdrawal of antiparkinsonian drugs and deep brain stimulation surgery

Abstract: Background: Parkinsonism-hyperpyrexia syndrome (PHS) is a rare but potentially fatal condition in patients with Parkinson's disease. Deep brain stimulation (DBS) is a widely used and efficacious treatment for advanced Parkinson's disease. Case presentation: Here, we report a case of PHS in a patient who first underwent withdrawal of antiparkinsonian medications and then bilateral subthalamic nucleus DBS. Conclusions: Patients should be advised to gradually decrease rather than suddenly stop antiparkinsonian me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(11 reference statements)
0
1
0
1
Order By: Relevance
“…Regarding PHS in the perioperative period, Han et al reported a 69-year-old female patient who developed worsening PD symptoms despite being on medical therapy [ 27 ]. The patient was a good candidate for STN-DBS and underwent surgery after her PD medications were withheld preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding PHS in the perioperative period, Han et al reported a 69-year-old female patient who developed worsening PD symptoms despite being on medical therapy [ 27 ]. The patient was a good candidate for STN-DBS and underwent surgery after her PD medications were withheld preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Se relaciona con el bloqueo de receptores dopaminérgicos o a la disminución de los precursores (5) dopaminérgicos a nivel central . Se caracteriza por un cuadro clínico distintivo de cambios en el estado (6) mental, rigidez, fiebre y disautonomía . La mortalidad es resultado de las manifestaciones de las (7) alteraciones autonómicas de la enfermedad y de las complicaciones sistémicas .…”
Section: Las Vías Dopaminérgicasunclassified